Potential of Pineapple Madu Shell (Ananas comosus (L.) Merr.) As Anti-Browning Agent in Apples Manalagi (Malus sylvestris Mill) - Rizka Devi Anggita; Zulkifli Zulkifli; Martha L Lande (Politeknik Negeri Lampung., 2017)
The purpose of this study was to determine the effect of water extract of pineapple shell in the process of browning apple manalagi (Malus sylvestris Mill). The research was conducted from October to November 2016 in the Laboratory of Plant Physiology Department of Biology, Faculty of Mathematics and Natural Sciences, University of Lampung. As variables were browning index, total soluble carbohydrate content, dehydrogenase enzyme activity, and reducing sugar levels, while the parameter is the mean of all variables. The experiment was conducted in completely randomizes design. The main factor was the water extract of the pineapple shell with 5 concentration levels: 0% v / v, 25% v / v, 50% v / v, 75% v / v, 100% v / v. Levene test, analysis of variance and LSD test was carried out at 5% significance level. The results showed that the water extract pineapple shell was significantly lower the browning index of apples manalagi, and the relationship between the concentration and browning index is quadratic (y = 9E-05x2 - 0.013x + 1.018 R² = 0665). Extract of pineapple shell did not significantly affect total soluble carbohydrate content of apples manalagi but a downward trend in total soluble carbohydrate content with increasing concentrations of the extract (y = -0.049x + 29.66 R² = 0.923). The relationship between the concentration of water extract pineapple shell with dehydrogenase enzyme activity was negative linear (y = -0.082x + 12.04 R² = 0.969). Reducing sugar levels increase at the concentration of 50% v/v,75% v/v, and 100% v/v. The final conclusion was that the water extract of pineapple shell was potential as anti-browning agent for apples manalagi because it was able to reduce browning index 51.89%, and influence other physiological processes.Keywords: Pineapple shell, Apples manalagi, Browning, carbohydrate, dehydrogenase.